Isolated splenomegaly during remission in childhood acute lymphoblastic leukemia - Özsoylu, Şinasi; Hiçsönmez, Gönül; Koçak, Nurten; Zamani, Vahide Prozorova (The Turkish Journal of Pediatrics, 1985)
Persistent splenomegaly was observed in two boys, aged 10 and 15 years, with acute lymphoblastic leukemia, beginning seven and eight months after induction of complete remission. Portal hypertension (410 mm/H₂O and 210 mm/H₂O) was documented in both during splenoportography. No evidence of liver disease or infiltration was shown by liver biopsy or liver function tests, and the splenic needle biopsy examination did not disclose any infiltrative disease four years after leukemia was diagnosed. We believe splenoportography and portal blood flow determinations should be carried out in patients with isolated splenomegaly during remission from acute lymphoblastic leukemia, if no other cause can be found.